Evaluation of neck blast resistance and agronomical performances on double haploid rice population in greenhouse and endemic field - GUT WINDARSIH; DWINITA WIKAN UTAMI (Smujo International, 2017)
Windarsih G, Utami DW. 2017. Evaluation of neck blast resistance and agronomical performances on double haploid rice population in greenhouse and endemic field. Nusantara Bioscience 9: 371-377. Blast disease caused by fungal Pyricularia grisea Sacc. is one of the most destructive diseases of rice in the world. The development of blast-resistant rice varieties will be essential to control this disease. This research aimed (i) to compare the resistance response to neck-blast among DH lines from double cross IR54/Parekaligolara//Bio110/Markuti and the differential varieties against three selected Indonesian blast races in greenhouse, (ii) to identify the gene(s) that caused the resistance to neck-blast based on the association between the resistance response and the genotype evaluation using molecular markers linked to Pi1, Pi33, Pib, Pir4 and Pir7 genes, and (iii) to evaluate the resistance response to leaf and neck blast on DH lines in endemic field (Sukabumi) and the agronomical performance of selected DH lines in optimum field in Ciasem of Subang, West Java, Indonesia during December 2013 to March 2014. Eleven double haploid lines from double-crossing IR54/Parekaligolara//Bio110/Markuti, the differential varieties as resistant control and the US2 variety for susceptible control were observed for neck-blast resistance response to three blast races in greenhouse and endemic field (Sukabumi), while the agronomical performances were observed in field of Ciasem-Subang. The results based on the genotyping evaluation, leaf and neck blast resistance, either in greenhouse and endemic location, and the agronomical performance in field showed that 5 selected double haploid lines had leaf and neck blast resistance and good performance on field trial. Thus they are promising for use either for further testing forwarding into releasing variety or used as donor for further blast resistant breeding activities.